Multiple Team Membership (MTM) Implementation in the Construction Industry at D.K.I Jakarta, Indonesia; A Case Study Analysis - Jennyamor Ramadhani; Ahyar Yuniawan (Petra International Journal of Business Studies, 2021)
The number of activities in construction projects is increasing where the pace of development follows the development of rising funds with shorter time constraints. As a result, businesses have reacted by allocating people to numerous teams simultaneously. The purpose of this study is to explore the implementation of multiple team membership and the performance of workers as individuals and teams in the construction industry, especially in DKI Jakarta. In addition, this study also explores the appropriate approach to use so that projects carried out using MTM can run smoothly. This research employed qualitative research with a case study approach also used a structured interview method with purposive sampling of 20 workers. The location is in the construction industry in DKI Jakarta. It was found that the implementation of MTM on employees with higher positions provided more benefits than employees with lower positions. The benefits for higher employees are getting paid more, more insight, more relationships, and bids for future projects. Meanwhile, employees in lower positions only get broader insights. In addition, it was also found that the appropriate approach to use so that MTM projects can run smoothly is to improve multitasking abilities and manage schedules and strategies.